Quantum Codes From Negacyclic Codes over Group Ring (Fq + vFq)G - Koroglu, Mehmet E.; Siap, Irfan (IOP PUBLISHING LTD, 2016)
In this paper, we determine self dual and self orthogonal codes arising from negacyclic codes over the group ring (F-q + vF(q))G. By taking a suitable Gray image of these codes we obtain many good parameter quantum error-correcting codes over F-q.
Keywords: Physics